2020
DOI: 10.1186/s12887-020-02420-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of irreducible aspects in developmental hip dysplasia by magnetic resonance imaging

Abstract: Background The developmental dysplasia of the hip (DDH) can cause a wide range of pathological changes, and often requires surgical treatment. Preoperative evaluation is very important for DDH. We aimed to assess the diagnostic capability of magnetic resonance imaging (MRI) for irreducible aspects preventing hip reduction in DDH. Methods A total of 39 pediatric patients who received DDH evaluation in pediatric orthopedics from January 2015 to Decem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Sexual minorities were more likely to be in the moderate or high suicidal ideation and suicide attempt trajectories (Trajectories 2 and 3), which is consistent with previous studies (Marshal et al 2013 ; Nkansah-Amankra 2013 ). Our results add to a growing body of research documenting the temporal changes of suicidal behaviors from a life course perspective (Liu et al 2020 ). Sexual minority youth experienced higher-risk suicidal trajectories than their heterosexual counterparts starting from early adolescence.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Sexual minorities were more likely to be in the moderate or high suicidal ideation and suicide attempt trajectories (Trajectories 2 and 3), which is consistent with previous studies (Marshal et al 2013 ; Nkansah-Amankra 2013 ). Our results add to a growing body of research documenting the temporal changes of suicidal behaviors from a life course perspective (Liu et al 2020 ). Sexual minority youth experienced higher-risk suicidal trajectories than their heterosexual counterparts starting from early adolescence.…”
Section: Discussionsupporting
confidence: 69%
“…Extant research, however, fails to address sociodemographic disparities in suicidal trajectories (Alegria et al 2010 ). Moreover, with increasing awareness of diversity and inclusion in suicide research (Moutier 2020 ; Park et al 2020 ), growing evidence demonstrates disproportionately and routinely greater risks of suicidal behaviors among individuals with intersecting identities across sex, race/ethnicity, sexual orientation, and socioeconomic status (Liu et al 2020 ; Moutier 2020 ; Mueller et al 2015 ). The growing rates of suicide attempts among Black adolescents, for example, were faster among Black girls than their male counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…If the volunteers were female, they should remove their underwear to avoid metal artifacts. They were asked to keep their bodies still during the scanning and avoid motion artifacts [ 11 ]. The exercise method is as follows: adopt simple Roman stool to do goat stand up movement, namely, the upper body antigravity flexion and extension movement.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 The shape of the labrum can be determined by arthrography 17 or magnetic resonance imaging (MRI). 18 However, arthrography is an invasive examination, and MRI is costly, and the patients need sedation. This study reviewed preoperative pelvic radiographs and the labrum shape on MRI of children with DDH.…”
mentioning
confidence: 99%
“…Other reports suggested that avascular necrosis of the femoral head after DDH surgery was related to the inversion of the labrum 15,16 . The shape of the labrum can be determined by arthrography 17 or magnetic resonance imaging (MRI) 18 . However, arthrography is an invasive examination, and MRI is costly, and the patients need sedation.…”
mentioning
confidence: 99%